(3TQM UMjM GdHNGQis - (3Ydj Hf Nda Hf YHO Gdedc Hf HWGd GdeZQHj GdbQWHi GdeGdcj , GHf nHnqWGd , J (B449 (3g` s; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B: (3HGH hbJ GdXgQ YfO GdRhGd hbGd LGHQ (B: (3cGf GdfHi Udi Gddg Ydjg hSde jUdi GdXgQ HGdgGLQI s
(3BNQgG (B:s
(3jfJgi HHGH ef de jUd GdVMi hQBg hGSYkG aGdJRGegG dgG dG jchf EdG Yf Yde ef GdfHi Udi Gddg Ydjg hSde Je GdSaQ GdKGfi jJdhg HGH UdGI GdVMi ai Gd MVQ ai GdLRA GdKGdK Ef TGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs